Analisis Kesalahan Mahasiswa Terhadap Penggunaan Verba Kureru dan Morau Sebagai Verba Bantu (Hojodoushi) - Wulandari Wulandari; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis is a descriptive research which examines erors made by the third year students of the Japanese study programe, education faculty, Riau University in learning Japanese languange particurarly in grammar and vocabulary. The erors in thesis both areas: grammar and vocabulary observe because of the different of the L1 and L2 and edition the verb kureru and morau has the same meaning with Indonesian.The aim of this study is to discovery what tipe of erors made by student and the factors contribute to the occurance of erors using. This research uses statistic descriptive inferencial with the percentage model to proces the colletive data.The finding explain that big percentage of the students have mad erors in using verb kureru and morau that function as auxiliary verbs. The clearly observed erors are in selecting which verbs are appropriately used and placing the subject, object and particle properly.The causes of the erors are due to lack of competence of the students in mastering the use of verbs in sentences using kureru and morau. The research concluded that more than of students experienced erors which have been evident from the 48,8 % percentage of erors rate. Far than more in general third year students of Japanese education, Riau University, only gain more fully comprehensive the lexical meaning of kureru and morau than sintaxical patterns.Key word : kureru, morau, giving and receiving